THE EFFECT OF PRESSURE ON PARTITIONING OF NI AND CO BETWEEN SILICATE AND IRON-RICH METAL LIQUIDS: A DIAMOND-ANVIL CELL STUDY - Bouhifd M.A.; Jephcoat A.P. (My University, 2003)
High-pressure and high-temperature experiments have been conducted with a laser-heated diamond-anvil cell (LHDAC) to determine the partition coefficients for Ni and Co up to 42 GPa and around 2500 K. Comparison of the present experimental data with those of multi-anvil devices shows a good agreement between the different exchange partitioning coefficients. The agreement suggests conditions in LHDAC experiments can reproduce those of multi-anvil experiments in the pressure range studied. Up to the maximum pressure reached in our work, Ni and Co become less siderophile with increasing pressure, as already observed in previous studies at lower pressures. Our data, combined with lower-pressure results, suggest a magma ocean would have extended to as much as 45 GPa (near 1200 km in depth) in order to obtain homogeneous equilibrium between core-forming metals and the silicate mantle in the early Earth.
Keywords: EARTH'S CORE FORMATION; LASER-HEATED DIAMOND-ANVIL CELL; HIGH-PRESSURE; MAGMA OCEAN; METAL-SILICATE SEGREGATION; SIDEROPHILE ELEMENTS